﻿Biotechnological approaches for sustainable production of astragaloside I, II and IV from endemic species of Astracantha aitosensis (Ivan.) and Astragalus membranaceus (fisch.) by in vitro cultures - Preslav Enchev; Yancho Zarev; Iliana Ionkova (Pensoft Publishers, 2023)
This study investigates the bioproduction of astragalosides I, II and IV from endemic Astracantha aitosensis (arnacantha) and Astragalus membranaceus species, and the biotechnological methods for increased efficiency. The extracts from established in vitro cultures, including A. aitosensis callus, shoots and roots and A. membranaceus hairy roots, showed higher astragaloside concentrations than native roots. Specifically, in vitro A. aitosensis cultures produced astragaloside I and II at 0.06 and 0.10 mg/g DW, which were absent in native roots. The production of A. membranaceuss hairy roots exceeds 8 to 15 times astragaloside I and II (0.80 and 0.90 mg/g DW) production when compared to native roots (0.10 and 0.05 mg/g DW), and around 3 times high amount related to astragaloside IV. Addressing astragaloside production challenges, this research also reveals biotechnology approaches as an alternative for sustainable production of this rare cycloartane saponins, conserving the natural habitats. A pilot reproducible in vitro cellular platform has been created, and protocol for specific, unconventional induction of the biosynthesis of the desired target compounds, exploiting the enzymatic system of plant cells from the unexplored plant species A. aitosensis has been established. Our findings clearly show the possibility of using in vitro cultures of A. aitosensis and A. membranaceus for biotechnology production of cycloartane type saponins.